2018
DOI: 10.1002/lno.10812
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal regulation of the coupling between photosynthetic electron transport and carbon fixation in the Southern Ocean

Abstract: Active fluorescence measurements can provide rapid, non‐intrusive estimates of phytoplankton primary production at high spatial and temporal resolution, but there is uncertainty in converting from electrons to ecologically relevant rates of CO2 assimilation. In this study, we examine the light‐dependent rates of photosynthetic electron transport and 13C‐uptake in the Atlantic sector of the Southern Ocean to derive a conversion factor for both winter (July 2015–August 2015) and summer (December 2015–February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 114 publications
2
21
0
Order By: Relevance
“…Spearman correlation and nMDS analyses revealed that PAR indeed had the highest correlation coefficient with K C ( Supplementary Table 2; Supplementary Figure 6, r = 0.66, p < 0.001), which is consistent with our previous results (Zhu et al, 2016(Zhu et al, , 2017. Changes in light availability drive an increase in the need to dissipate absorbed excitation energy through nonphotochemical dissipation (McKew et al, 2013) and hence a positive association between K C and NPQ may also be expected, as broadly observed previously (Schuback et al, 2015(Schuback et al, , 2016(Schuback et al, , 2017Hughes et al, 2018b;Ryan-Keogh et al, 2018). Since the K C of this study was derived from ETR and primary productivity in daily scales, similar to the method applied for daily ETR calculation, we also integrated the NPQ NSV values according to their light dependent functions (Supplementary Figure 7A).…”
Section: Phytoplankton Size Related Etr Production and K C Variatiosupporting
confidence: 91%
See 2 more Smart Citations
“…Spearman correlation and nMDS analyses revealed that PAR indeed had the highest correlation coefficient with K C ( Supplementary Table 2; Supplementary Figure 6, r = 0.66, p < 0.001), which is consistent with our previous results (Zhu et al, 2016(Zhu et al, , 2017. Changes in light availability drive an increase in the need to dissipate absorbed excitation energy through nonphotochemical dissipation (McKew et al, 2013) and hence a positive association between K C and NPQ may also be expected, as broadly observed previously (Schuback et al, 2015(Schuback et al, , 2016(Schuback et al, , 2017Hughes et al, 2018b;Ryan-Keogh et al, 2018). Since the K C of this study was derived from ETR and primary productivity in daily scales, similar to the method applied for daily ETR calculation, we also integrated the NPQ NSV values according to their light dependent functions (Supplementary Figure 7A).…”
Section: Phytoplankton Size Related Etr Production and K C Variatiosupporting
confidence: 91%
“…However, no positive relationship between NPQ NSV and K C was evident for this data set ( Supplementary Figure 7B). Lack of a relationship (or negative relationship) between NPQ or PAR with K C was also reported before (Schuback et al, 2017;Ryan-Keogh et al, 2018). Whilst the reason is not well-known yet, it may reflect a decoupling of the NPQ NSV (or PAR)-K C relationship under relatively low light (Schuback et al, 2017) and further investigation is needed.…”
Section: Phytoplankton Size Related Etr Production and K C Variatiomentioning
confidence: 87%
See 1 more Smart Citation
“…Region Iron level Growth rate, d −1 A B C D α B under iron limitation has been observed previously with O 2based measurements of photosynthesis (20), but not with the short-term (hours) 14 C-based method (21)(22)(23). The difference in the results of the two methods may be linked to the fact that the shortterm 14 C method measures neither gross nor net C-fixation rates, while the O 2 method measures rates of photosynthetic O 2 production minus O 2 consumption from respiration and photorespiration, which may be lessened under iron and light limitation (24,25).…”
Section: Speciesmentioning
confidence: 69%
“…Depth‐integrated PP rates (PP wc , mol C·m −2 ·day −1 ) were calculated from quenching corrected glider‐derived chlorophyll (Thomalla, Moutier, et al, ) and PAR according to Platt et al (), Platt and Sathyendranath (), and Thomalla et al (). PP parameters were determined from a linear relationship with chlorophyll using experimental values from both cruises (supporting information Figure S2; Ryan‐Ryan‐Keogh, Thomalla, Little, et al, ). Seasonal variation in nutrient concentrations within the euphotic and winter mixed layer isopycnals required three different methods to derive depth‐integrated nutrient inventories.…”
Section: Methodsmentioning
confidence: 99%